About Exiles and Entryisms: The Case of the Formation of the Spanish PST - Aiziczon, Fernando (Hispania Nova, 2024)
This article reconstructs the trajectory of the political current that founded the Spanish Socialist Workers Party in 1979. In the beginning, Spanish Trotskyist militants came into contact with Argentine militants in exile belonging to the Argentine Socialist Workers Party, and after adhering to its guidelines they decided to join (entrism) the Spanish Socialist Workers Party (PSOE) first, and the Communist League. Revolutionary (LCR), later. However, these experiences occurred crossed by discussions about the path of the Spanish transition, the validity of the armed route in political processes, and the dynamics of entryism itself. Using party documents and oral interviews, our investigation seeks to trace the militant trajectory of this organization and outline the characteristics of a left-wing political culture whose common feature, in addition to ideological affinity, was that of being experiences in transit between dictatorships and democracy.
Keywords: PST; trotskyism; exile; entryism; PSOE; LCR